Opportunities and challenges of bacterial extracellular vesicles in regenerative medicine - Jiming Guo; Zhijie Huang; Qinjing Wang; Min Wang; Yue Ming; Weixing Chen; Yisheng Huang; Zhengming Tang; Mingshu Huang; Hongyu Liu; Bo Jia (Journal of Nanobiotechnology)
Abstract Extracellular vesicles (EVs) are membrane-bound vesicles that are shed or secreted from the cell membrane and enveloped by a lipid bilayer. They possess stability, low immunogenicity, and non-cytotoxicity, exhibiting extensive prospects in regenerative medicine (RM). However, natural EVs pose challenges, such as insufficient targeting capabilities, potential biosafety concerns, and limited acquisition pathways. Although engineered EVs demonstrate excellent therapeutic efficacy, challenges such as low production yield and the complexity of engineering modifications constrain their further clinical applications. Bacteria have advantages such as rapid proliferation, diverse gene editing methods, mature cultivation techniques, and relatively easy preparation of bacterial EVs (BEVs), which can be used to effectively address the challenges currently encountered in the field of EVs. This review provides a description of the biogenesis and pathophysiological functions of BEVs, and strategies for optimizing BEVs preparation to attain efficiency and safety are discussed. An analysis of natural characteristics of BEVs is also conducted to explore how to leverage their advantages or mitigate their limitations, thereby overcoming constraints on the application of BEVs in RM. In summary, engineered BEVs possess characteristics such as high production yield, excellent stability, and high drug-delivering capabilities, laying the foundation for their application in RM. Graphical Abstract